DEEPFAKE DAN DISTORSI RUANG PUBLIK DIGITAL: ANALISIS TEORI PUBLIC SPHERE JURGEN HABERMAS - Muhammad Albar Nagara (Jurnal Komunikasi & Media Digital, 2025)
This study analyzes the impact of deepfake technology on the digital public sphere through Jurgen Habermas' public sphere theory. Deepfake, an AI-driven manipulation tool, enables hyper-realistic yet deceptive videos, leading to misinformation, political propaganda, and privacy violations. Social media, particularly YouTube, has become a key platform for the spread of deepfake content, distorting rational discourse and eroding public trust. Using a qualitative, descriptive-analytical approach, this research examines how deepfake disrupts digital communication and challenge the principles of an open public sphere. The findings emphasize the urgent need for digital literacy, regulatory frameworks, and AI-powered detection systems to mitigate its negative impacts. Strengthening awareness and institutional responses is crucial in maintaining a transparent and credible digital public sphere. This study contributes to discussions on media ethics, communication strategies, and policymaking to counteract the risks posed by deepfake technology.